QUOTE UNQUOTE: CHAPTER DEFINING QUOTES IN WATTPAD - Khilya Tifani Yumna; Gelyn Puti Yunita; Nur Liza; Anggraini; Noni Dwi Setyawati; Halima Anjayani; Olivia Zalianty (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
This study examines the role of quotes at the beginning of chapters in stories shared on Wattpad, focusing on their alignment with chapter content and overall narrative unity. Utilizing DeFrank's (2019) categorization of strong and weak quotes, along with Coley's (2015) theory of narrative alignment and Christman's (2004) concept of narrative unity, the research evaluates how quotes influence storytelling. Strong quotes, characterized by direct and emotionally impactful language, enhance reader engagement and thematic cohesion. In contrast, weak quotes, which are general or indirect, contribute less to narrative alignment but can still support thematic exploration. By analyzing examples from various Wattpad stories, the study highlights the use of quotes as tools for foreshadowing and emotional resonance. The findings underscore the importance of quote selection in shaping the reader's experience, providing insights into their role in digital storytelling. This research offers implications for enhancing narrative strategies on interactive platforms and suggests further exploration into the integration of text and visuals in digital media.